Longitudinal survey of antibiotic stewardship practices in Wisconsin nursing homes, before and after a policy change - Alissa E. Balke; Victoria L. Griffin; Diane Dohm; Brenda J. Ryther; Linda L. McKinley; Raymond P. Podzorski; Anna M. Marciniak; Christopher J. Crnich; Lindsay N. Taylor (Cambridge University Press, 2022)
The Centers for Medicare and Medicaid mandated that nursing homes implement antibiotic stewardship programs (ASPs) by November 2017. We conducted surveys of Wisconsin nursing-home stewardship practices before and after this mandate. Our comparison of these surveys shows an overall increase in ASP implementation efforts, but it also highlights areas for further improvement.